Platelet-Rich Plasma Therapy Enhances the Beneficial Effect of Bone Marrow Stem Cell Transplant on Endometrial Regeneration - Zhou, Ying; Shen, Huaxiang; Wu, Yuelin; Zhao, Xiaobo; Pei, Jindan; Mou, Zhengqian; Dong, Jinhua; Hua, Xiaolin (Frontiers in Cell and Developmental Biology, 2020)
This study aimed to investigate the potential effect of platelet-rich plasma (PRP) therapy on treatment using bone marrow stem cell (BMSC) transplant for uterine horn damage, and to reveal the potential underlying molecular mechanism. Uterine horn damage was established in a rat model, which can be repaired by transplant using BMSCs receiving control or PRP treatment. Immunohistochemistry was conducted to evaluate thickness and expression of α-SMA and vWF in the regenerated endometrium tissues. mRNA and proteins of insulin-like growth factor-1 (IGF-1) and interleukin-10 (IL-10) were measured both in the regenerated endometrium tissues and in cultured BMSCs to evaluate the effect of PRP treatment on their expression. Enzyme-linked immunosorbent assay was employed to measure the secretory levels of IL-10 in cultured BMSCs. Multi-differentiation assays were performed to address the effect of PRP treatment on tri-lineage potential of cultured BMSCs. Chromatin immunoprecipitation and luciferase reporter assays were applied to analyze NF-κB subunit p50 binding on IL-10 promoter and the resulted regulatory effect. PRP treatment significantly improved the efficacy of BMSC transplant in repairing uterine horn damage of rats, and elevated IGF-1 and IL-10 expression in regenerated endometrium tissues and cultured BMSCs, as well as enhanced tri-lineage differentiation potential of BMSCs. On the other hand, p50 inhibition and silencing suppressed the PRP-induced expression and secretion of IL-10 without affecting IGF-1 in the BMSCs. Furthermore, p50 was able to directly bind to IL-10 promoter to promote its expression. Data in the current study propose a working model, where PRP therapy improves endometrial regeneration of uterine horn damage in rats after BMSC transplant therapy, likely mediated through the NF-κB signalling pathway subunit p50 to directly induce the expression and production of IL-10.